2019
DOI: 10.3390/v11020175
|View full text |Cite
|
Sign up to set email alerts
|

Tropism of the Chikungunya Virus

Abstract: Chikungunya virus (CHIKV) is a re-emerging mosquito-borne virus that displays a large cell and organ tropism, and causes a broad range of clinical symptoms in humans. It is maintained in nature through both urban and sylvatic cycles, involving mosquito vectors and human or vertebrate animal hosts. Although CHIKV was first isolated in 1953, its pathogenesis was only more extensively studied after its re-emergence in 2004. The unexpected spread of CHIKV to novel tropical and non-tropical areas, in some instances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 211 publications
(295 reference statements)
3
101
0
2
Order By: Relevance
“…In order to validate these findings in a more relevant cell line for human infection, we next investigated the cytotoxic and antiviral potential of tomatidine in Huh7 cells (human hepatic cell line) as hepatocytes are targets during natural CHIKV infection 25 . Furthermore, like with Vero-WHO, these cells are also commonly used in antiviral CHIKV studies 13,[26][27][28] .…”
Section: Resultsmentioning
confidence: 99%
“…In order to validate these findings in a more relevant cell line for human infection, we next investigated the cytotoxic and antiviral potential of tomatidine in Huh7 cells (human hepatic cell line) as hepatocytes are targets during natural CHIKV infection 25 . Furthermore, like with Vero-WHO, these cells are also commonly used in antiviral CHIKV studies 13,[26][27][28] .…”
Section: Resultsmentioning
confidence: 99%
“…CHIKv infections are not usually associated with congenital abnormalities, although the development of microcephaly after birth in CHIKv-infected neonates has been reported 220,225 . Rare cases of placental and transplacental CHIKv infection have also been reported, and resulted in abortion 226 . alphaviral arthralgia, with such endeavours hopefully leading to new therapeutic approaches.…”
Section: Box 3 | Mother-to-child Infectionsmentioning
confidence: 99%
“…Indeed, muscle satellite cells together with fibroblasts, osteoblasts, endothelial cells, and macrophages would be among the cells targeted during acute infection of CHIKV [102,103]. Hussain et al confirmed this model for pathogenesis based on human primary myoblasts [94].…”
Section: Chikungunya Virusmentioning
confidence: 95%